The small molecule alpha-synuclein misfolding inhibitor, NPT200-11, produces multiple benefits in an animal model of Parkinson's disease. Issue 1 (December 2018) - Price, Diana; Koike, Maya; Khan, Asma; Wrasidlo, Wolfgang; Rockenstein, Edward; Masliah, Eliezer; Bonhaus, Douglas
Abstract Accumulation of alpha-synuclein (ASYN) in neurons and other CNS cell types may contribute to the underlying pathology of synucleinopathies including Parkinson's disease (PD), dementia with Lewy bodies (DLB) and Multiple Systems Atrophy (MSA). In support of this hypothesis for PD, ASYN immunopositive aggregates are a prominent pathological feature of PD, and mutations and gene multiplications of human wild type (WT) ASYN cause rare familial autosomal-dominant forms of PD. Targeted therapeutics that reduce the accumulation of ASYN could prevent or slow the neurodegenerative processes in PD and other synucleinopathies. NPT200-11 is a novel small molecule inhibitor of ASYN misfolding and aggregation. The effects of NPT200-11 on ASYN neuropathology were evaluated in animal models over expressing human alpha synuclein. Longitudinal studies using retinal imaging in mice expressing a hASYN::GFP fusion protein revealed that 2 months of once daily administration of NPT200-11 (5 mg/kg IP) resulted in a time-dependent and progressive reduction in retinal ASYN pathology. The effects of NPT200-11 on ASYN pathology in cerebral cortex and on other disease-relevant endpoints was evaluated in the Line 61 transgenic mouse model overexpressing human wild type ASYN. Results from these studies demonstrated that NPT200-11 reduced alpha-synuclein pathology in cortex, reduced associated neuroinflammation (astrogliosis), normalized striatal levels of the dopamine transporter (DAT) and improved motor function. To gain insight into the relationship between dose, exposure, and therapeutic benefit pharmacokinetic studies were also conducted in mice. These studies demonstrated that NPT200-11 is orally bioavailable and brain penetrating and established target plasma and brain exposures for future studies of potential therapeutic benefit.